A method of monitoring of the bulb of quinoa plantations orientated to the dosing of the water volume for drip irrigation systems - Phellan, Eduardo; Gutiérrez, Justiniano; Soto Jeri, Jonell; Capuñay, Simon; López, Jorge; Del Carpio, Christian (Institute of Electrical and Electronics Engineers, 2022)
7 páginas